Dampak Work-Life Integration Terhadap Kesejahteraan Karyawan Dan Produktivitas Kerja : A Systematic Literature Riview - Muhammad Ikram Idrus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The complexity of the modern work environment in the technological era requires organizations to adapt for sustainability. Easy access to technology also poses challenges for human resources in balancing work and personal life. The shift from work-life balance to work-life integration has become a hot issue for in-depth discussion. Several studies indicate that disparities in work-life integration lead to high work-related stress (burnout) among employees. This study conducts a thorough analysis of the impact of work-life integration on employee welfare and work productivity. By gathering 10 relevant articles published in trusted media over the past 10 years (2013-2023), we found that integrating work and personal life positively influences and plays a crucial role in improving employee welfare. Digitalization helps employees be more productive at different times and places. The same is proven with the relationship between work-life integration and work productivity positively affecting, especially for employees with good technological adaptation skills. Kata Kunci : work-life Integration, Employee welfare, work productivity.